Mental health nursing - Gorman, Linda M.; Anwar, Robynn F. (Philadelphia, PA : F.A. Davis Company, 2022)
'The Sixth Edition of Mental Health Nursing is a psychiatric nursing text tailored specifically to the needs of the Licensed Practical Nurse/ Licensed Vocational Nurse (LPN/LVN) student. We understand that many students at this level of preparation do not have the opportunity for clinical experience in a psychiatric setting, but they will encounter patients with mental health issues in their rotations and throughout their careers. Students will encounter patients and their families with psychiatric diagnoses as well as a variety of psychosocial issues and behaviors that challenge them. This text provides the basic knowledge and skills to address many of these challenges, with an emphasis on communication'--
History of Mental Health Nursing -- Basics of Communication -- Ethics, Evidence-Based Practice, and Regulations -- Developmental Psychology Throughout the Life Span -- Sociocultural Influences on Mental Health -- Nursing Process in Mental Health -- Stress, Coping, and Defense Mechanisms -- Medications and Other Therapies -- Complementary and Alternative Treatment Modalities -- Anxiety, Somatic Symptom Disorders, and Post-Traumatic Stress Disorder -- Depressive Disorders -- Bipolar Disorders -- Suicide -- Personality Disorders -- Schizophrenia Spectrum and Other Psychotic Disorders -- Neurocognitive Disorders: Delirium and Dementia -- Substance Use and Addictive Disorders -- Eating Disorders -- Childhood and Adolescent Mental Health Issues -- Postpartum Issues in Mental Health -- Aging Population -- Victims of Abuse and Violence.
Preceded by Neeb's mental health nursing / Linda M. Gorman, Robynn F. Anwar. Fifth edition. 2019.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on March 10, 2023).
WorldCat record variable field(s) change: 050
Keywords: Psychiatric nursing -- Methodology; Mental illness -- Treatment; Practical nurses; Mental Disorders -- nursing; Psychiatric Nursing -- methods; Licensed Practical Nurses; Nursing, Practical -- methods; Mental illness -- Treatment; Practical nurses; Electronic books